PELATIHAN PEMBUATAN BUSANA RUMAH PADA PESERTA BLK KOTA PADANGSDIMPUAN - Elfi Husnita Hasibuan; Khairunnisa Butar - butar; Nurlaila -; Olivia Feby Mon Harahap (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Abstract Training on making home clothes is one of the efforts to increase human resources, especially mothers, in this case BLK participants in Padangsidimpuan City. This skill can be used as a filler in spare time and used as a business opportunity that can increase income for household life. The aim of the research is to describe the instructor's activities, learning outcomes and the responses of the trainees. This type of research is quasi-experimental research with a One Shot Case Study design. The training was held in 2 meetings. Data collection methods used are observation and questionnaires. Analysis of instructor activity data used the mean value, learning outcomes and participant responses used percentages. The results of the research on the instructor's activities during the training for making home clothes got a very good mean. Mean Instructor activity at meeting I got 3.76 good category (Good) and meeting II got 4.05 very good category (SB). The learning outcomes of the participants were seen from the process starting from cutting patterns, placing patterns, cutting materials, moving pattern marks, sewing pockets, slits, sides, fitting I and II, was 85% in the Very Good category (SB), while taking measurements, making patterns, sewing the hem, neatness is 70% Good category (B) and the resulting negligee is 50% Good category (B). The results of the participants' response to the negligee making training were 100% very good (SB), participants felt happy, useful, needed further development, the instructor's activities made it easier to make negligee, and on time, the material was easy to understand, which was new. It can be concluded that the instructor's activities as a whole are good, the learning outcomes are good and the response of the trainees is very good. Abstrak Pelatihan pembuatan busana rumah merupakan salah satu upaya peningkatan Sumber Daya Manusia khususnya ibu-ibu dalam hal ini peserta BLK Kota Padangsidimpuan. Keterampilan ini dapat dijadikan sebagai pengisi waktu luang dan dijadikan sebagai peluang usaha yang dapat menambah penghasilan bagi kehidupan rumah tangga. Tujuan penelitian adalah mendeskripsikan aktifitas instruktur, hasil belajar dan repon peserta pelatihan. Jenis penelitian ini adalah penelitian eksperimen semu dengan desain One Shot Case Study. Pelatihan dilaksanakan 2 kali pertemuan. Metode pengumpulan data yang digunakan adalah observasi dan angket. Analisis data aktifitas instruktur menggunakan nilai mean, hasil belajar serta respon peserta menggunakan persentase. Hasil penelitian aktifitas instruktur selama pelatihan pembuatan busana rumah mendapatkan mean sangat baik. Mean Aktifitas instruktur pertemuan I Mendapatkan 3,76 kategori baik (Baik) dan pertemuan II mendapatkan 4,05 kategori Sangat Baik (SB). Hasil belajar peserta dilihat dari proses mulai dari memotong pola, meletakkan pola, memotong bahan, memindahkan tanda pola, menjahit saku, belahan, sisi, pengepasan I dan II, adalah 85% kategori Sangat Baik (SB), sedangkan mengambil ukuran, membuat pola, menjahit belahan, kerapian adalah 70% kategori Baik (B) dan hasil jadi daster adalah 50% kategori Baik (B). Hasil respon peserta terhadap pelatihan pembuatan daster 100% sangat baik (SB), peserta merasa senang, bermanfaat, perlu dikembangkan lebih lanjut, aktivitas instruktur mempermudah pembuatan daster, dan tepat waktu, materi mudah dipahami, merupakan hal baru. Dapat disimpulkan bahwa aktifitas instruktur secara keseluruhan adalah baik, hasil belajar baik dan respon peserta pelatihan sangat baik.